(untitled) (Philosophy and Progress, 2021)
The protection of environmental human rights demands an ethical governance frame work. This paper examines the characteristics of three governance models and argues that development planners and policymakers can employ deliberative governance that is nourished by public participation to protect environmental human rights in Bangladesh. The deliberative governance will pave the way to ecological modernization, implement ecologically sustainable development goals, and, in turn, ensure freedom, fairness and good governance since human societies desire to flourish human life. Philosophy and Progress, Vol#63-64-; No#1-2; Jan-Dec 2018 P 1-28